Estimation of Hydrazone Derivative Compounds as Anti-Bacterial Agents Against Staphylococcus aureous Through Molecular Docking and Self Consisted Field - Frimayanti, Neni; Octaviani, Melzi; Wulandari, Gety; Zamri, Adel (Trends in Sciences, 2023)
Molecular docking is an important computational method for drug design. It can be used to predict the binding interaction of receptor with the ligand. Hydrazone were reported as chemical compounds with =CH-N-NH group. In addition, hydrazone derivative compounds were also reported have various activities, such as antibacterial agents against Staphylococcus aureus. S. aureus is a very serious problem because this bacteria is increasingly resistant to various types of antibiotics (multidrug resistance). S. aureus is also having extraordinary adaptability thus, it can be resistant to many antibiotics. The purpose of this study is to predict whether the hydrazone compounds were active as anti-bacterial agents and also to ensure that the binding interaction is stable before and after docking calculation. Molecular docking research was conducted using the protein target 1N67 (PDB ID), which was derived from the crystallographic structure of hydrazone derivative chemicals. Four hydrazone derivative substances were docked to the protein in this investigation with grid boxes along x, y, and z radii of 67, 86 and 66, respectively. The positive control was chloramphenicol. Self-Consisted Field (SCF) was calculated using AM1 as basis set and molecular dynamic simulation was performed using CHARMM27 force field. The results showed that from 4 tested compounds, only compound 3 with the binding free energy of −6.535 kcal/mol was estimated as active agent against S. aureus. This compound showed very good potential to be an anti-bacterial with the lowest binding free energy value with the highest stability level. HIGHLIGHTS Due to in silico study such as molecular docking, molecular dynamic simulation is an important computational method for drug design. It can be used to predict the binding orientation of small molecule drug candidates to their protein targets. In addition, docking is also can be applied to predict small molecule affinity and activity. Thus, molecular docking has an important role in drug discovery and rational design The ligand interaction with the receptor was more stable due to the decreased binding free energy value The lowest binding free energy and lowest RMSD value of this molecule, which may presumably cause compound 3 to has better binding affinity compare to other compounds GRAPHICAL ABSTRACT